Pengembangan Perangkat Pembelajaran Matematika Berbasis Kemampuan Pemecahan Masalah untuk Siswa SMA Kelas XI - Wilibaldus Bhoke; Maria Editha Bela (Departement of Mathematics Education, 2023)
The purpose of this study was to develop learning tools for online mathematics learning based on problem solving abilities for the XI grade high school level using the valid and practical ADDIE development model. This type of research is research on developing mathematics learning tools that describe validity (learning tools) and practicality (learning implementation). The device development model uses the ADDIE model which consists of analysis, design, development, implementation, and evaluation. This research was conducted at SMAS Citra Bakti. The research subjects were students of class XI, totaling 36 people. The instrument used in this study is the validity sheet. The results showed that the learning tools used in this study were, first, the validity of the mathematics learning tools for lesson plans and worksheets were declared valid and feasible to use. Second, the practicality of learning tools is taken from observational data on the implementation of learning in each meeting. Thus it can be concluded that the learning tools developed are declared valid and practical for use in learning mathematics.